PTH and Vitamin D Repress DMP1 in Cementoblasts. (October 2015) - Wang, L.; Tran, A.B.; Nociti, F.H.; Thumbigere-Math, V.; Foster, B.L.; Krieger, C.C.; Kantovitz, K.R.; Novince, C.M.; Koh, A.J.; McCauley, L.K.; Somerman, M.J.
A complex feedback mechanism between parathyroid hormone (PTH), 1, 25(OH)2 D3 (1, 25D), and fibroblast growth factor 23 (FGF-23) maintains mineral homeostasis, in part by regulating calcium and phosphate absorption/reabsorption. Previously, we showed that 1, 25D regulates mineral homeostasis by repressing dentin matrix protein 1 (DMP1) via the vitamin D receptor pathway. Similar to 1, 25D, PTH may modulate DMP1, but the underlying mechanism remains unknown. Immortalized murine cementoblasts (OCCM.30), similar to osteoblasts and known to express DMP1, were treated with PTH (1–34). Real-time quantitative polymerase chain reaction (PCR) and Western blot revealed that PTH decreased DMP1 gene transcription (85%) and protein expression (30%), respectively. PTH mediated the downregulation of DMP1 via the cAMP/protein kinase A (PKA) pathway. Immunohistochemistry confirmed the decreased localization of DMP1 in vivo in cellular cementum and alveolar bone of mice treated with a single dose (50 µg/kg) of PTH (1–34). RNA-seq was employed to further identify patterns of gene expression shared by PTH and 1, 25D in regulating DMP1, as well as other factors involved in mineral homeostasis. PTH and 1, 25D mutually upregulated 36 genes and mutually downregulated 27 genes by ≥2-fold expression ( P ≤ 0.05). Many identified genes were linked with the regulation of bone/tooth homeostasis, cell growth and differentiation, calcium signaling, and DMP1 transcription. Validation of RNA-seq results via PCR array confirmed a similar gene expression pattern in response to PTH and 1, 25D treatment. Collectively, these results suggest that PTH and 1, 25D share complementary effects in maintaining mineral homeostasis by mutual regulation of genes/proteins associated with calcium and phosphate metabolism while also exerting distinct roles on factors modulating mineral metabolism. Furthermore, PTH may modulate phosphate homeostasis by downregulating DMP1 expression via the cAMP/PKA pathway. Targeting genes/proteins mutually governed by PTH and 1, 25D may be a viable approach for designing new therapies for preserving mineralized tissue health.